The Role Of Trust In The Relationship Between Purchase Intention And Perceived Corporate Social Responsibility In Mobile Shopping Applications - Intan Yuniarti Ningsih; Yolanda Masnita; Kurniawati; Alvian Satria Ramadan; I Gede Billy Ambara Putra (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Consumer purchasing behavior in mobile shopping applications has been considerably altered by the quick development of e-commerce, which has been greatly impacted by the adoption of Corporate Social Responsibility (CSR) activities. With an emphasis on the mediating function of consumer trust qualities, including kindness and integrity, this study examines the relationship between CSR and purchase intention. The data collected from 316 respondents through an online survey were analyzed quantitatively using Structural Equation Modeling (SEM). The results show that CSR has a favorable and substantial effect on consumer trust, which raises purchase intention. Additionally, it has been demonstrated that trust successfully moderates the relationship between CSR and purchase intention. According to the study's findings, incorporating strong CSR practices is crucial for building consumer involvement and trust, influencing purchase intentions, and giving Indonesian mobile shopping platforms a competitive edge.